Pengembangan Sistem Point of Sales Berbasis Laravel Filament Menggunakan Metode Pengembangan Aplikasi Cepat - Farid Syafi Razzaq; Andriyan Rizki Jatmiko (SMATIKA JURNAL : STIKI Informatika Jurnal, 2026)
Digital transformation is increasingly essential for improving operational efficiency and data accuracy in Micro, Small, and Medium Enterprises (MSMEs). However, MSMEs often face a dual challenge: the need for rapid system implementation and the limited technical literacy of system users, which creates a gap between complex system requirements and practical usability. This study applies and evaluates the effectiveness of the Rapid Application Development (RAD) methodology in developing a web-based Point of Sale (POS) system tailored to MSME operational characteristics. The research adopts an applied, design-oriented approach, emphasizing iterative prototyping and continuous user involvement to reduce adoption barriers. Rather than focusing on feature completeness, the study examines how RAD supports system usability and user acceptance among non-technical users. The proposed system was evaluated using the System Usability Scale (SUS) involving users with different operational roles. The results indicate that the iterative nature of RAD effectively bridges the gap between system complexity and user capability, as reflected by an average SUS score of 76.66, categorized as “Good”. These findings provide empirical evidence that RAD is a suitable development approach for MSME information systems, particularly in contexts requiring rapid deployment and high usability, and contribute to applied information systems research by highlighting the role of user-centered iteration in improving system acceptance.